Clinical Trial of the Phytoestrogen-rich Herb, Pueraria mirifica as a Crude Drug in the Treatment of Symptoms in Menopausal Women - Muangman, Verasing; Cherdshewasart, Wichai (Siriraj Medical Journal, 2020)
The clinical trial to evaluate the estrogenic effects of the crude drug derived from dry powder of a phytoestrogen-rich Thai herb Pueraria mirifica (White Kwao Krua) in five female volunteers with menopausal symptoms showed that the crude drug clearly improved the signs and symptoms related to menopause such as, hot flushes, frustration, sleep disorder, skin dryness, high blood cholesterol, oligomenorrhoea and amenorrhoea, with no change in the blood cells, liver and kidney functions, as well as other physiological status after four months of treatment. In four volunteers, treatments were continued to complete the one-year test period with half the dose and was found to maintain their satisfied menopausal relief status. The crude drug dosage was administered at 200 mg daily for three weeks a month during the first four months of treatment and 200 mg every other day for 20 days per month for the remaining of eight months. These doses were effective and safe as phytoestrogen treatment of menopausal symptoms.